Analysis of Water Content Profiles in Arctic Mixed-Phase Clouds during VERDI - Lauermann, Felix; Finger, Fanny; Ehrlich, André; Wendisch, Manfred (Universität Leipzig, 2016)
Airborne measurements of liquid water content (LWC) and ice water content (IWC) were performed in mixed-phase clouds during the field campaign VERDI in Canada in April and May 2012. In single-layer and multi-layer clouds different vertical profiles of LWC and IWC could be observed. For single layer clouds the maximum LWC occurred in the upper half of the clouds while the IWC had a maximum near the cloud base. This pattern was attributed to the sedimentation of ice particles. In the lowest cloud layer of a multi-layer system both LWC and IWC reached a maximum near cloud top. Together with measured particles size distributions this suggests the presence of the seeder-feeder-process described by Fleishauer et al. (2012) for mid-level clouds. Im Rahmen der VERDI-Kampagne im April und Mai 2012 in Kanada wurden flugzeuggetragene Messungen von Flüssigwassergehalt (LWC) und Eiswassergehalt (IWC) durchgeführt. Für Einschicht- und Mehrschichtwolkensysteme konnten unterschiedliche Vertikalprofile von LWC und IWC nachgewiesen werden. In Einschichtsystemen wurden die größten Flüssigwassergehalte in der oberen Wolkenhälfte und die größten Eiswassergehalte nahe der Wolkenunterkante gemessen. Diese Verteilung wurde auf die Sedimentation von Eispartikeln zurückgeführt. In der untersten Wolkenschicht eines Mehrschichtsystems befanden sich die Maxima von LWC und IWC nahe der Wolkenoberkante. Diese Beobachtung deutet zusammen mit gemessenen Partikelgrößenverteilungen auf das Vorhandensein des Seeder-Feeder- Prozesses hin, welcher von Fleishauer et al. (2012) für mittelhohe Wolken beschrieben wurde.